APLIKASI PENGOLAHAN DATA PENDUDUK DESA KOTA KANDIS DENDANG - Nurjani, Yeni (FORTECH (Journal of Information Technology), 2017)
This explain the scientific wraiting Processing Application of data population with the aim of facilitating the creationof aun report, it is necessary for an Application Data Processing Family Planning Program which aims to make it easier to create data reports perekapan Family Planning and reduce errors - errors in data collection. Planning data processing system is susatu data processing system to perform data collection for population. The results of the study showed that the office of Women and Family Planning empowerment requires a data processing application . This system is made by using the Application Programming Languages ââBorland Delphi 7.0 with its database using Microsoft Office Access and report output using QReport. For good results of data processing , fast and kenerja data processing can be improved and the design of the face is obtained more easily.